Basic implications on three pathways associated with SARS-CoV-2 - Jong hoon Lee; Consolato Sergi; Richard E. Kast; Badar A. Kanwar; Jean Bourbeau; Sangsuk Oh; Mun-Gi Sohn; Chul Joong Lee; Michael D. Coleman (Biomedical Journal)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) interacts between the host and virus and govern induction, resulting in multiorgan impacts. Its pathophysiology involves the followings: 1) the angiotensin-converting enzyme (ACE2) and Toll-like receptor (TLR) pathways: 2) the neuropilin (NRP) pathway: 3) the spike protein pathway. Therefore, it is necessary to block the pathological course with modulating innate lymphoid cells against diverse corona variants in the future.